The social nominalism of neo-liberalism and conservative social trends - Шоріна, Т. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article examines the social, ethical, anthropological foundations of the policies and practices of contemporary neo-liberalism. It isjustified that in ideological and morally-valued sense the neoliberal model contains a reversible orientations and in transformed wayrevives past socio-historical practice.